Non-cytotoxic systemic treatment in malignant peripheral nerve sheath tumors (MPNST): A systematic review from bench to bedside. (June 2019) - Martin, Enrico; Lamba, Nayan; Flucke, Uta E.; Verhoef, C.; Coert, J. Henk; Versleijen-Jonkers, Yvonne M.H.; Desar, Ingrid M.E.
Highlights: To date, no systemic treatment has yet proven clinical efficacy in MPNSTs. In vivo studies show promising results targeting PI3K/Akt/mTOR and VEGFR pathways. Oncolytic viruses may also play a role in future treatment of MPNSTs. Combination of drugs will likely be key to maximize treatment effects. Several ongoing trials recruiting MPNST patients may bring further insights. Abstract: Background: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas. Once metastasized, prognosis is poor despite regular treatment with conventional cytotoxic drugs. This study reviews the preclinical and clinical results of non-cytotoxic systemic therapy in MPNST. Methods: A systematic search was performed in PubMed and Embase databases according to the PRISMA guidelines. Search terms related to 'MPNST', 'targeted therapy', 'immunotherapy', and 'viral therapy' were used. Only in vivo studies and clinical trials were included. Clinicaltrials.gov was also searched for any ongoing trials including MPNST patients. Qualitative synthesis was performed on all studies stratifying per target: membrane, cytoplasmic, nuclear, immunotherapy and oncolytic viruses, and other. In vivo studies were assessed for treatment effect on tumor growth (low/intermediate/high), survival, and metastases. Clinical trials were assessed on response rate, progression-free survival, and overall survival. Results: After full-text screening, 60 in vivo studies and 19 clinical trials were included. A total of 13 trials are ongoing and unpublished. The included trials displayed relatively poor response rates thus far, with patients achieving stable disease at best. Inhibiting cytoplasmic targets most commonly yielded high treatment effect, predominantly after mTOR inhibition. Oncolytic viruses and angiogenesis inhibition also demonstrate intermediate to high effect. Therapies including a combination of drugs were most effective in controlling tumor growth. Several ongoing trials investigate potentially promising pathways, while others have yet to be established. Conclusion: Targeting the PI3K/Akt/mTOR pathway seems most promising in the treatment of MPNSTs. Oncolytic viruses and angiogenesis inhibition represent emerging therapies that require further study. Combinations of targeted therapies are most likely key to maximize treatment effect.